Pengaruh Penggenangan Pada Berbagai Fase Pertumbuhan Kedelai (Glycine Max (L.) Merr) Terhadap Pertumbuhan dan Produksi - Bangun Tampubolon; Joedojono Wiroatmodjo; Justika S Baharsjah; . Soedarsono (Forum Pasca Sarjana, 1989)
The soybean (Glycine rnax (L.) Merr) plant is able to make morphological adaptations to flooding such as the formation of adventive roots. Long-term continuous flooding result in reductive conditions in the rhizosphere which is detrimental to plant growth. This experiment was conducted to investigate the influence of flooding at various stages of soybean development on growth and yield of the crop on Alluvial and Red Yellow Podsolic soils. Flooding invariably resulted in the reduction of the net assimilation rate and yield of soybean. Reduction depended on the time and duration of flooding. Flooding during active vegetative growth (PI), flowering-pod filling (P2), seed ripening (P3), active vegetative growth and flowering-pod filling (P4), active vegetative growth and seed ripening (PS), flowering-pod filling and seed ripening (P6), and active vegetative growth until seed ripening (P7) respectively resulted yield reductions of 20.42, 50.74, 9.43, 46.68, 30.28, 52.63 and 35.26% compared to the unflooded control. The number and dry weight of root nodules and nitrogen fixation rate were highest in the P4 and P7 treatments. Nodules were formed on the adventive roots, when the soybean plants were flooded.